2020
DOI: 10.3233/jbr-190422
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic, nutritional and anti-carcinogenic characteristics of the fruit and rooting performance of cuttings of black mulberry (Morus nigra L.) genotypes

Abstract: BACKGROUND: Black mulberry fruits have high antioxidant capacity, exhibiting health protective properties. In order to exploit their entire dynamic though, elite genotypes must be vegetatively propagated. OBJECTIVE: The purpose was to assess the physiological, organoleptic, phytochemical and anti-carcinogenic (only of the best two genotypes) properties of eleven new black mulberry genotypes, compared to the elite hybrid Fengchisang and the possibility of easy asexual propagation through semi-hardwood and hardw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
10
1
Order By: Relevance
“…Approximately 0.5 g of the frozen strawberry pulp was extracted twice with 5 mL 50% (v/v) methanol in an ultrasonic bath for 15 min each time and then centrifuged. After the second centrifugation, the two supernatants were combined and assessed for total phenolic compounds according to Roussos et al [22]. The total phenols, total o-diphenols, total flavanols, and total flavonoids are expressed as mg equivalent of gallic acid (GAE), caffeic acid (CAE), catechin (CtE), and caffeic acid per g fresh weight, respectively.…”
Section: Total Phenol Content Total Anthocyanin Content Individual An...mentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 0.5 g of the frozen strawberry pulp was extracted twice with 5 mL 50% (v/v) methanol in an ultrasonic bath for 15 min each time and then centrifuged. After the second centrifugation, the two supernatants were combined and assessed for total phenolic compounds according to Roussos et al [22]. The total phenols, total o-diphenols, total flavanols, and total flavonoids are expressed as mg equivalent of gallic acid (GAE), caffeic acid (CAE), catechin (CtE), and caffeic acid per g fresh weight, respectively.…”
Section: Total Phenol Content Total Anthocyanin Content Individual An...mentioning
confidence: 99%
“…After the second centrifugation, the supernatants were combined and used for the determination of both total anthocyanins (by the pH differentiation method) and individual anthocyanins. The total anthocyanin content was assessed according to Roussos et al [22] and the results are expressed as pelargonidin 3-glucoside 100 g −1 fresh weight. For the individual anthocyanins, a portion of the supernatant was filtered through a 0.24 µm pore size syringe filter and analyzed with an HPLC.…”
Section: Total Phenol Content Total Anthocyanin Content Individual An...mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the acetonic and methanolic extracts of M. nigra and M. alba fruits were analyzed for their phenolic compounds, and results showed that acetonic and methanolic extracts of M. nigra have the highest contents of total phenolics (173 mg/g and 164 mg/g, respectively) [28]. Finally, genotypes strongly influence the chemical content and antioxidant capacity of M. nigra [23, 29]. Comparing the levels of organic acids, sugars, vitamin C, and phenolic compounds in 3 genotypes of this plant showed that there is a significant difference between the genotypes regarding the amounts of these compounds [23].…”
Section: Phytochemical Profile Of M Nigramentioning
confidence: 99%